Synthesis and characterisation of rare earth substituted bismuth vanadate solid electrolytes - Lee, C.K; Ong, C.S. (Elsevier, 1999)
The compositional ranges of Bi4V2O11 solid solutions containing rare earth elements: Nd, Gd, Er and Yb have been determined by means of a phase diagram study at solidus temperatures, ≈900°C. The locus of the solid solutions indicates that rare earth elements replace V in the crystal structure and the new family of oxide ion conductors has the overall formula Bi4+yV2-x-yMxO11-y-x. DTA studies confirmed the identity of the various polymorphs formed. AC impedance studies show that Nd-, Gd-, Er- and Yb-doped materials are oxide ion conductors; however, they are electrically inhomogeneous. The best conductors, irrespective of the dopants, have compositions with y=0 and x=0.2 with conductivity values of up to 2×10-4 Ω-1 cm-1 at 300°C.